Rumah-rumah Tok Ku Paloh, D62, Paloh Makam Tok Ku, Cabang Tiga, Kuala Terengganu, Terengganu - Othman Mohd. Noor; Mohd. Nazri Sidek; Roswadi Abd. Rashid; Wan Mohd. Zailani Wan Arifin @ Wan Daud; Lim, Jo Soon; Chan, Chee Soon; Lee, Chiong Meng; Ngadinah Saparun; Norbiah Abd Holed; Noor Ismail; Thor, Siew Kok (Sekudai : UTM, 1991)
02